Management of Thoracic Empyema with Pleuroscopy in Lung Cancer Patient - Putra, Christian Surya Eka; Setyawan, Ungky; Putra, Ngakan (Universitaas Brawijaya, 2022)
Background: Thoracic empyema is a serious complication related to death at young age and old age. The most common cause of thoracic empyema is parapneumonic effusion, and lung cancer is a rare cause of empyema. Pleuroscopy as an invasive procedure is often indicated as a second option for therapeutic purposes after chest tube insertionCase: We reported one case at Dr. Saiful Anwar, a man, 61 years old, was diagnosed with lung cancer with recurrent pleural effusions. Then after receiving chemotherapy, the patient was hospitalized again because of his worsening condition. From the lateral chest X-ray, a complex hydropneumothorax was obtained. Thoracentesis procedure revealed a greenish-yellow cloudy pleural fluid. The patient underwent pleuroscopy to evaluate the cause of empyema and drainage of pus. Necrotic tissue and pleural surface with nodules were found on pleuroscopy. The results of the anatomical pathology examination from pleural biopsy showed suppurative inflammation with several atypical cellsConclusion: Management of empyema must be carried out as soon as possible and appropriately. Pleuroscopy can be performed as a diagnostic and therapeutic measure in cases of thoracic empyema caused by lung cancer